The Development of Visible‐Light Photoredox Catalysis in Flow. Issue 4 (8th April 2014) - Garlets, Zachary J.; Nguyen, John D.; Stephenson, Corey R. J.
Abstract Visible‐light photoredox catalysis has recently emerged as a viable alternative for radical reactions otherwise carried out with tin and boron reagents. It has been recognized that by merging photoredox catalysis with flow chemistry, slow reaction times, lower yields, and safety concerns may be obviated. While flow reactors have been successfully applied to reactions carried out with UV light, only recent developments have demonstrated the same potential of flow reactors for the improvement of visible‐light‐mediated reactions. This review examines the initial and continuing development of visible‐light‐mediated photoredox flow chemistry by exemplifying the benefits of flow chemistry compared with conventional batch techniques.